Comprehensive metagenomic and lipidomic analysis showed that baicalin could improve depressive behaviour in atherosclerotic mice by inhibiting nerve cell ferroptosis - Ren, Peng; Zhao, Yulong; Li, Xue; Xie, Jing; Liao, Xingxing; Luo, Qiang; Liu, Xu; Li, Jiameng; Fan, Yuzhen; Cheng, Xinyi; Fu, Xinyao; Zhou, Junjie; et al. (Frontiers in Immunology, 2025)
BackgroundAtherosclerosis (AS) concomitant depression is a serious clinical problem with unclear mechanisms of co-morbidity. Baicalin (BA) can resist atherosclerosis and depression by regulating intestinal flora and host lipid metabolism. Therefore, based on intestinal microorganisms and lipid metabolism, this study explored the mechanism of baicalin against AS concomitant depression.Methods16 C57BL/6 mice were fed with normal diet as blank control group. 48 ApoE-/-mice were randomly divided into 3 groups (model group and BAL, BAH two treatment groups). The mouse model of atherosclerosis concomitant depression was established by high-fat feeding combined with restraint stimulation for 16 weeks. Behavioural experiments and biochemical indexes were used to detect the antidepressant effect and anti-atherosclerosis effect of baicalin. Metagenomic sequencing technology combined with metabolomics analysis was used to detect the effects of BA on intestinal microflora structure and brain lipids in AS co-depressed mice. Erastin was used to induce HT-22 hippocampal neurons to construct a model of ferroptosis. The inhibition of baicalin on ferrotosis was verified by detecting the cell viability, ROS production, and expression levels of glutathione, SLC7A11, GPX4 and ACSL4 in each group.ResultsBaicalin could effectively improve the indexes of AS co-depressed mice, and the results of metagenomics and lipidomics showed that there were disorders of intestinal flora represented by Helicobacter_typhlonius and Escherichia_coli and disorders of lipid metabolism represented by PE in the AS co-depressed model mice. The correlation analysis showed that the lipid metabolism disorders in the model mice were closely related to the intestinal flora disorders, and baicalin intervention could effectively improve the intestinal flora and lipid metabolism disorders in the AS co-depressed mice. Metabolic pathway enrichment analysis showed that differential lipid PEs were significantly enriched in the iron death pathway, and our further in vitro cellular experiments showed that baicalin could inhibit Erastin-induced Ferroptosis in the hippocampal neuronal cell line HT-22 by promoting the expression of SLC7A11, GSH, and GPX4, inhibiting the expression of ACSL4, and decreasing the cellular ROS.ConclusionBaicalin improves intestinal microbiota and brain lipid metabolism and inhibits ferroptosis of nerve cells, which possesses the application value of anti-atherosclerotic concomitant depression.